Políticas sobre drogas: uma análise da intervenção profissional dos policiais militares da Paraíba sob a ótica da prevenção - PROERD - Negreiros, Janaina Cipriano do Nascimento (2017)
The present study one consists in a Master's thesis in Social Service, tied the Federal University of the Paraíba, whose construction, had the objective to map the production of knowledge of relative the Social Service the thematic one of the aging. Thus, we look for to identify to the contribution of the profession in relation the social matter of the oldness and in the plan of the debates and theoretical reflections we search to identify to which the thematic associations and the boardings of analysis, “biological/behavioural”, “economics”, socioculturlista and “transdisciplinary”, proposals for the authors Siqueira (2001); Siqueira, Botelho and Coelho (2002), had prevailed in this production. From a theoretical inquiry, we treat initially on the aspects that involve the aging while expression of the social matter and later the production of knowledge in the scope of the Social Service, as well as the insertion of the thematic one in this production. In regards to the methodological procedures, we adopt in this study bibliographical the documentary research and and use as parameter, the study of Lima and Mioto (2007), whose analysis developed for the reading technique following the following stages: reading of recognition and exploration of the material, selective reading, critical or reflexive reading and finally, the interpretative reading. For the mapping of the data, we appeal the bases of the Scielo, Latindex and Lilacs, with focus for periodic online of the Social Service with Qualis, in the period of 1996 the 2015, where the articles had been selected on the basis of the describers “aging”, “oldness”, “aged” and “aged”. Considering that the production of the knowledge is reflected, of the demands ece of fishes in the reality, Notably in the Sociocupational spaces of the social assistants, we verify that predominant the thematic direction in this production of the knowledge if developed in the optics of the “Rights/Social Protection”, “Work” and “Social Politics”. The result of the research demonstrated a trend of the Social Service in analyzing the question of the oldness, in a perspective of social construction, where it looked for to apprehend in the interior of the society, the constant representations and attributions in the movement of this category. However, we ahead consider that of the complexity that involves the aging process, to prioritize definitive aspects of the oldness has greater probability of these publications if to Distancing of the complexity of the facts, therefore, becomes necessary a more integral debate, in way that the boardings of analyses if complement.